Prolonged co-existence of 'archaic' and 'modern' Palaeozoic ophiuroids – evidence from the early Permian, Southern Carnarvon Basin, Western Australia. (2nd September 2018) - Hunter, Aaron W.; McNamara, Kenneth J.
Abstract : The discovery of a very large ophiuroid (disk diameter of 80 mm) in the early Permian (Kungurian) Cundlego Formation in the Southern Carnarvon Basin of Western Australia extends the stratigraphical range of 'archaic' ophiuroids unequivocally into the Permian, unlocking a lost fossil record of this group. Hitherto such ophiuroids have been discovered preserved articulated from strata no younger than the late Carboniferous. Herein we describe the new ophiuroid as Teleosaster creasyi gen. et sp. nov. Although existing temporally with Permian ophiuroids with a 'modern' morphological architecture, Teleosaster was biogeographically separated. This 'archaic' ophiuroid persisted in high latitude seas, suggesting such 'archaic' forms were displaced from the shallow-water, low latitude niches by the 'modern' ophiuroids. In modern oceans, ophiuroid gigantism similar to that in Teleosaster creasyi is typically only expressed in cold, high latitude oceans. It has been argued that the frequent occurrence of gigantism in such environments is due to the much lower levels of predation pressure. Unlike other echinoderm classes, the morphological and ecological transformation that resulted in the evolution of 'modern' ophiuroids had already taken place well before the events of the Permo–Triassic mass extinction. With the increase in diversity of durophagous predators in low latitude shallow-water communities during the mid-Palaeozoic Marine Revolution, we argue that 'archaic' ophiuroids were more susceptible to these higher levels of predation than the 'modern' forms and were displaced into regimes of lower predation pressure in high latitude oceans. http://zoobank.org/urn:lsid:zoobank.org:pub:E4FD9264-127D-4995-AD12-C9721F212FCD